CLINICAL CHARACTERISTICS OF DRIVING PHOBIA - Ehlers, A; Hofmann, S; Herda, C; Roth, W (1994)
Fifty-six subjects who were afraid of driving were recruited by advertisement and compared to 31 controls without this fear. Subjects were interviewed and given several questionnaires to gather information for making DSM-III-R diagnoses and to determine their agoraphobia avoidance behavior, driving history, and the history of their phobia. Our sample had a mean age of 48, was 82% female, and typically feared and avoided driving on freeways, bridges, and through tunnels, but were not so fearful about driving on quiet residential streets. Diagnostically, 81% of the phobics reported having had panic attacks, but only 14% (8/56) met criteria for Panic Disorder. Although on average phobics had had no more automobile accidents than controls, 15% (8/55) reported an accident as the primary reason for their phobia. The 53% (29/55) who reported panic attacks as the primary reason for their phobia were more concerned about anxiety symptoms while driving than phobics who gave other, nonaccident-related reasons for their phobia. We conclude that many driving phobics do not fit neatly into current DSM-III-R anxiety disorder categories, because they combine characteristics of Simple Phobia and Panic Disorder with Agoraphobia without meeting the criteria for either disorder. © 1994.